2013
DOI: 10.1186/ar4265
|View full text |Cite
|
Sign up to set email alerts
|

Double-antiangiogenic protein DAAP targeting vascular endothelial growth factor A and angiopoietins attenuates collagen-induced arthritis

Abstract: IntroductionAngiogenesis plays a critical role in synovial inflammation and joint destruction in rheumatoid arthritis (RA). Vascular endothelial growth factor A (VEGF-A) and angiopoietins are two important mediators of synovial angiogenesis. We have previously developed a novel chimeric decoy receptor, namely, double-antiangiogenic protein (DAAP), which can both bind VEGF-A and angiopoietins and block their actions. This study was performed to evaluate the antiarthritic effect of DAAP and the combination effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Hence, Trebananib is currently being tested in clinical trials for the cancer treatment [179]. Double anti-angiogenic protein (DAAP), a dimeric decoy receptor with strong binding affinity to Ang1, Ang2 and VEGF [180], could markedly reduce CIA joint vascularization. However, the effect of Trebananib and DAAP on RA patients remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Trebananib is currently being tested in clinical trials for the cancer treatment [179]. Double anti-angiogenic protein (DAAP), a dimeric decoy receptor with strong binding affinity to Ang1, Ang2 and VEGF [180], could markedly reduce CIA joint vascularization. However, the effect of Trebananib and DAAP on RA patients remains undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Neovascularization, or angiogenesis, is a complex process leading to formation of new blood vessels from the pre-existing vascular network of the tissue. Synovial angiogenesis may plays a critical role in the early stage of RA by promoting inflammatory cell infiltration and the development of pannus, aggressive tumor like fibrovascular granulation tissue, which eventually leads to joint destruction [ 4 7 ]. However, the molecular mechanisms, which participate in the promotion of the angiogenesis in rheumatoid arthritis, have not been identified [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the function of VEGF is concentrated and has stronger specificity (27). VEGF may additionally increase permeability of blood capillaries and is the blood vessel anti-reflection molecule that exhibits the strongest biological effect, >5 million times more potent compared with histamine substances (28). The results of the present study suggested that gambogic acid significantly suppressed the activation of VEGF protein expression, blocking activation of the VEGF signaling pathway in RA rats.…”
Section: Discussionmentioning
confidence: 56%
“…It is an endothelial cell mitogen and promotes fission of endothelial cells in order to promote neovascularization. The VEGF receptor is located in vascular endothelial cells (28). Therefore, the function of VEGF is concentrated and has stronger specificity (27).…”
Section: Discussionmentioning
confidence: 99%